2022
DOI: 10.1007/s10461-022-03744-z
|View full text |Cite
|
Sign up to set email alerts
|

“Yes, I’m reminded, but it doesn’t mean I’m taking them”: Experiences with Short Message Service Reminder Use in Real-time Monitoring of HIV PrEP among Young Women in Kenya

Abstract: z. The Version of Record is the version of the article after copy-editing and typesetting, and connected to open research data, open protocols, and open code where available. Any supplementary information can be found on the journal website, connected to the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The level of acceptability of SMS reminders in this study was comparable with that reported in a Kenyan study among pregnant women initiated on PrEP where 94% reported that two-way SMS reminders were helpful and 95% reported that they would use them again after the study [ 21 ]. Additionally, a qualitative study conducted among trial participants using in-depth interviews following an SMS reminder intervention in Kenya also affirmed that SMS reminders are highly acceptable among AGYW taking PrEP [ 22 ]. Another study in central Ethiopia reported the acceptability of SMS reminders among 420 adult PLHIV to be high (91%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of acceptability of SMS reminders in this study was comparable with that reported in a Kenyan study among pregnant women initiated on PrEP where 94% reported that two-way SMS reminders were helpful and 95% reported that they would use them again after the study [ 21 ]. Additionally, a qualitative study conducted among trial participants using in-depth interviews following an SMS reminder intervention in Kenya also affirmed that SMS reminders are highly acceptable among AGYW taking PrEP [ 22 ]. Another study in central Ethiopia reported the acceptability of SMS reminders among 420 adult PLHIV to be high (91%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%